The Enlightened Brain: Novel Imaging Methods Focus on Epileptic Networks at Multiple Scales - Rossi, L. Federico; Kullmann, Dimitri M.; Wykes, Robert C. (Frontiers in Cellular Neuroscience, 2018)
Epilepsy research is rapidly adopting novel fluorescence optical imaging methods to tackle unresolved questions on the cellular and circuit mechanisms of seizure generation and evolution. State of the art two-photon microscopy and wide-field fluorescence imaging can record the activity in epileptic networks at multiple scales, from neuronal microcircuits to brain-wide networks. These approaches exploit transgenic and viral technologies to target genetically encoded calcium and voltage sensitive indicators to subclasses of neurons, and achieve genetic specificity, spatial resolution and scalability that can complement electrophysiological recordings from awake animal models of epilepsy. Two-photon microscopy is well suited to study single neuron dynamics during interictal and ictal events, and highlight the differences between the activity of excitatory and inhibitory neuronal classes in the focus and propagation zone. In contrast, wide-field fluorescence imaging provides mesoscopic recordings from the entire cortical surface, necessary to investigate seizure propagation pathways, and how the unfolding of epileptic events depends on the topology of brain-wide functional connectivity. Answering these questions will inform pre-clinical studies attempting to suppress seizures with gene therapy, optogenetic or chemogenetic strategies. Dissecting which network nodes outside the seizure onset zone are important for seizure generation, propagation and termination can be used to optimise current and future evaluation methods to identify an optimal surgical strategy.